Strategic Directions of the Development of Russian Regions: Issues of Economy, Accountance, Taxification, Economic Security, Theoretical and Applied Finance - Gritskevich T. I., Lavina T. A., Zakharova A. N., Kruglov V. N., Sitokhova T. E., Khachirov K. A., Turiev Z. V., Zhuplei I. V., Zadvorneva E. P., Shmidt I. I., Khazieva K. F., Iankovskaia D. G., Pinegina M. V., Galkina E. V., Soldatova L. I. (Strategic Directions of the Development of Russian Regions: Issues of Economy, Accountance, Taxification, Economic Security, Theoretical and Applied Finance, 2022)
the state and level of use of material resources are the consequence of the impact of all aspects of financial and economic activity. Taking into account the specifics of the printing house's activity as a system and as a process, recommendations are proposed to accelerate the turnover of material resources from the point of view of the production cycle. The results of the work have methodological value for commercial organizations in the practice of material resources management, in identifying reserves for increasing the efficiency of their use. The structural and logical scheme of the stages of the complex analysis of the material resources of the enterprise, taking into account the industry features, has been compiled and proposed. The method of analysis has been tested on the example of one of the printing enterprises. Recommendations are given to improve the efficiency of the use of material resources.
Keywords: материальные ресурсы; факторный анализ; factor analysis; методика экономического анализа; этапы анализа; отраслевой анализ; methodology of economic analysis; material resources; stages of analysis; industry analysis